2019
DOI: 10.1097/hnp.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Online Survey of Nurses' Personal and Professional Praying

Abstract: This study explored how nurses' prayer beliefs and practices are associated with their offering to pray with patients. Participants (N = 423) completed an online survey. Those with higher prayer experience scores were 9% more likely to offer prayer to patients; those working in religious settings were 2.5 times more likely offer prayer to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This finding indicates a need for education on how to document spiritual care correctly (Mamier, Taylor, & Winslow, 2019) and how to offer prayer to patient therapeutically (O'Connell-Persaud, Dehom, Mamier, Gober-Park, & Taylor, 2019). In addition, spiritual care education needs to include the varieties of prayers among patients from diverse religio-cultural backgrounds who want prayer (O'Connell-Persaud et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates a need for education on how to document spiritual care correctly (Mamier, Taylor, & Winslow, 2019) and how to offer prayer to patient therapeutically (O'Connell-Persaud, Dehom, Mamier, Gober-Park, & Taylor, 2019). In addition, spiritual care education needs to include the varieties of prayers among patients from diverse religio-cultural backgrounds who want prayer (O'Connell-Persaud et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…18 One study demonstrated that offering to pray for someone or keeping them in their prayers was particularly wel-comed by the recipients. 33 For those who recognize prayer as part of their mindfulness practice, exchanging prayers or requests for prayer via text may be welcomed. Spiritual wellbeing, religious or non-religious, leads not only to developing a sense of inner peace and transcendence through life' s challenges but also to providing more compassionate care to others.…”
Section: What Do I Say In a Text?mentioning
confidence: 99%
“…Prayer is one method of social support that may be exchanged through TM, and a significant majority of those who engage in prayer have reported this to be reassuring and helpful in improving their well-being 18. One study demonstrated that offering to pray for someone or keeping them in their prayers was particularly welcomed by the recipients 33. For those who recognize prayer as part of their mindfulness practice, exchanging prayers or requests for prayer via text may be welcomed.…”
Section: Supportive Tm In Actionmentioning
confidence: 99%
“…In teaching how to pray with and for patients, educators must incorporate ethical parameters. A first step is to explain and assist students to practice self-awareness of their own spirituality and prayer practices that might influence their caring (O'Connell et al, 2019). For example, "an offer of prayer may reflect the nurse's personal needs and way of addressing suffering, but not the patient's" (p. 133).…”
Section: Ethical Considerationsmentioning
confidence: 99%